Elementary statistics - Almeda, Josefina Venegas; Sarte, Genelyn Ma. Ferry ;Capistrano, Therese Garcia (Quezon City, Philippines : University of the Philippines, 2010)
These prophetic words of H.G. Wells inspired us to write a textbook for an introductory course in statistics.
Chapter 1. Introduction -- Chapter 2. Collection of Data -- Chapter 3. Sampling and sampling and sampling techniques -- Chapter 4. Presentation of data -- Chapter 5. Organization of Data -- Chapter 6. Measures of central tendency -- Chapter 7. Measures of location -- Chapter 8. Measures of dispersion -- Chapter 9. Measures of skewness and kurtosis -- Chapter 10. Introduction to probability theory -- Chapter 11. Sampling distributions -- Chapter 12. Exploratory data analysis -- Chapter 13. Estimation: Single population -- Chapter 14. Estimation: two populations -- Chapter 15. Tests of hypotheses: single population -- Chapter 16. Tests of hypotheses: two populations -- Chapter 17. Chi- Square tests -- Chapter 18. Simple Linear regression analysis -- Appendices.
Includes bibliographical references and index.
Keywords: STATISTICS